Pembuatan Kode Produk Untuk Inisiasi Program Barcode Pada Berbagai Produk Kerajinan Ukm Garuda Jaya : Bunga Kering Dari Klobot Jagung - Elvina Dhiaul Iftitah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
Product coding for various floral handicrafts from corn husk has been done by UKM Garuda Jaya. UKM Garuda Jaya as one of the creative producers of various floral handicraft is concerned to protect their products both in terms of authentication and for the purposes of administration and distribution in the market. Flower handicraft products from corn husk require a process of creative art and trained hand skills. Consistency to the shape, size and color selection of corn husk ingredients need to be maintained. Similarly, the standard manufacturing process stages need to be established. For this reason the product code should be created. Based on the identification and classification step toward various kind of flower crafts products of UKM Garuda Jaya, the products is divided into two groups. First group is flower buds and second group is flower arrangements. We obtained as much as 9 products of coding for flower buds (daisy, lotus, rose and ater) and 2 products of coding for flower arrangements (daisies, rice flowers and orchids)